Factors Influencing Teachers’ Motivation of English as a Foreign Language Instructors - Cigdem Fidan (Pascasarjana Universitas Negeri Makassar, 2023)
In education, the concern is often on students’ motivation for learning. However, motivation for teaching is also critical because teachers’ involvement, excitement, and motivation in the teaching process correlatively help students’ learning process. Applying a mixed-method research design, this study examines teachers’ motivation of English as a foreign language instructors working at public universities in the Southeast region of Turkey. An adapted Attitude of Motivation Test Battery was applied to 40 English as a foreign language instructors. Moreover, semi-structured interviews conducted with 20 participants, 5 classroom observations, and teacher diaries written by 2 participants were used to gather qualitative data. While Statistical Package of Social Sciences 15.0 was used to analyze quantitative data, content analysis was applied to analyze data gathered through semi-structured interviews, classroom observations, and teacher diaries. The results show that there are internal and external factors influencing teachers’ motivation. The results also show that despite the negative influence of some external factors on teachers’ motivation, instructors showed enthusiastic attitudes while teaching English. Therefore, the study suggests establishing professional standards and better physical conditions in and around the teaching contexts to increase the teachers’ motivation of English as a foreign language instructors teaching at public universities.